Effects of conditions on thе synthesis and properties of Bi-2234 HTSC ceramic produced from the melt - Д.Е. Ускенбаев; А.С. Ноғай; А.Д. Ускенбаев; Э.А. Ноғай (Қарағанды университетінің хабаршысы. Физика сериясы)
The article presents the results of a study aimed at obtaining the formation of superconducting phases and the formation of a high texture of particles that affect the current-carrying characteristics in ceramics of the composition Bi1.6Pb0.4Sr2Ca3Cu4Oy and the study of their properties. For the synthesis of ceramics, precursors from the glass phase were used, which were obtained by melting the starting material under the influence of radiant flux (IR radiation) and quenching the melt in a facility rotating at a speed of 3000 rpm. Platinum wire was used as a substrate. During the heat treatment of samples in the temperature range of 845–850 °C and a holding time of 72 hours (with intermediate grinding every 24 hours), the superconducting high-temperature phase Bi-2223 crystallized in the studied samples. Critical temperatures and resistances of superconducting samples were measured by the four-probe method by measuring the dependence of resistance on the temperature in the range from 300 K to 60 K.